2012
DOI: 10.1007/s10068-012-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a time-temperature integrator system using Burkholderia cepacia lipase

Abstract: A time-temperature integrator (TTI) is a device used to show a time-temperature dependent change that reflects the temperature history and quality status of the food to which it is attached. An enzymatic TTI system based on the reaction between Burkholderia cepacia lipase and tricaprylin, which causes a pH change, was developed. The temperature dependence of the response rate of this new lipase-type TTI was modeled using the Arrhenius equation, and the estimated activation energy was calculated as 70.61±11.10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The laccase TTI prototype and milk were incubated to simulate normal and abnormal storage temperatures 4 and 25 °C, and the temperature was switched every 8 h; 8 h of 4 °C followed by 8 h of 25 °C was regarded as one cycle, and three cycles were performed over 48 h. The results showed that the reaction rate ( k ) of laccase at 4 °C was lower than that at 25 °C in all cycles, except the first ( Figure 6 ), which indicated that the laccase TTI prototype exhibited a favorable response to temperature, and that the coloration was reproducible under temperature fluctuations. Temperature sensitivity was thus retained by the immobilized laccase during temperature fluctuations, and dynamic modeling performed through kinetic parameters and numerical analysis was effective; the present findings are similar to the results of a reaction kinetics study of a lipolytic enzyme TTI examined under dynamic temperature profiles [ 30 ]. Because the coloration of the laccase TTI prototype was considered to follow a first-order reaction, the initial reaction occurred quickly.…”
Section: Resultssupporting
confidence: 82%
“…The laccase TTI prototype and milk were incubated to simulate normal and abnormal storage temperatures 4 and 25 °C, and the temperature was switched every 8 h; 8 h of 4 °C followed by 8 h of 25 °C was regarded as one cycle, and three cycles were performed over 48 h. The results showed that the reaction rate ( k ) of laccase at 4 °C was lower than that at 25 °C in all cycles, except the first ( Figure 6 ), which indicated that the laccase TTI prototype exhibited a favorable response to temperature, and that the coloration was reproducible under temperature fluctuations. Temperature sensitivity was thus retained by the immobilized laccase during temperature fluctuations, and dynamic modeling performed through kinetic parameters and numerical analysis was effective; the present findings are similar to the results of a reaction kinetics study of a lipolytic enzyme TTI examined under dynamic temperature profiles [ 30 ]. Because the coloration of the laccase TTI prototype was considered to follow a first-order reaction, the initial reaction occurred quickly.…”
Section: Resultssupporting
confidence: 82%
“…Yan et al (2008) developed a new amylase-based TTI used for the food cold chain. Kim, Park, and Hong (2012) described an enzymatic TTI system based on the reaction between Burkholderia cepacia lipase and tricaprylin. Kim, Kim, and Lee (2012) developed an enzyme based TTI prototype that used laccase.…”
Section: Introductionmentioning
confidence: 99%
“…Because laccase follows simple discoloration kinetics (Huber and Carré, 2012), the color response to time-temperature variation was linearly proportional to the rate of color change, allowing direct and intuitive determination of the remaining shelf-life of food quality losses (Park et al, 2013). However, the major drawback of enzymatic TTI for monitoring chilled food shelf life is not only the narrow range of Ea, but also the Ea value is by no means comparable to that of food spoilage and deterioration (Tsoka et al, 1998;Bobelyn et al, 2006;Kim et al, 2012a;Kim et al, 2012b). Taoukis (2001) suggested that any TTI device with Ea within 25 kJ/mol from a food quality factor of interest could be acceptable to ensure accuracy of an enzyme TTI for prediction of the remaining shelf-life of food.…”
Section: Introductionmentioning
confidence: 99%